Rhodotorula benthica culture as an alternative to antibiotics improves growth performance by improving nutrients digestibility and intestinal morphology, and modulating gut microbiota of weaned piglets - Zhang, Qianqian; Li, Jian; Yi, Xin; Li, Zipeng; Liang, Shuang; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Wu, De; Che, Lianqiang (Frontiers in Microbiology, 2022)
The effects of Rhodotorula benthica culture (RBC) and antibiotics (AB) on the growth performance, nutrients digestibility, morphological indicators, and colonic microbiota of weaning piglets were explored. Ninety-six (Duroc × Landrace × Large) weaned piglets (21-day old) weighing 7.7 ± 0.83 kg, were randomly allocated into 4 dietary treatments. They were fed on basal diet (CON), basal diet + 25 ppm bacitracin zinc + 5 ppm colistin sulfate (AB), 5% reduction in soybean meal of basal diet + 5 g/kg RBC (RBC1) or 10% reduction in soybean meal of basal diet + 10 g/kg RBC (RBC2). The result showed that dietary RBC1 improved the body gain/ feed intake (G/F) of weaned piglets than CON diet, and RBC2 diet improved average daily gain and G/F than CON and AB diets from day 15 to 28 (P < 0.05). Supplementation of RBC2 improved the apparent total tract digestibility of dry matter, nitrogen, and gross energy in weaned piglets compared with controls from day 15 to 28 (P < 0.05). Dietary AB, RBC1, and RBC2 all improved the ileal villus height and villus height/ crypt depth, and the two indicators were greater in the RBC2 -treated piglets than those in the AB and RBC1 groups (P < 0.05). The serum superoxide dismutase activity was enhanced by dietary AB, RBC1, and RBC2 (P < 0.05). Glutathione concentration was elevated by dietary RBC1 and RBC2 (P < 0.05). According to 16S rRNA sequence analysis, AB -and RBC2-treated weaning piglets had a high relative abundance of Firmicutes and Lachnospiraceae in the colon digesta, and high Lactobacillus was found in RBC1-treated piglets. Additionally, RBC2 supplementation increased the α diversity (Chao1, PD-whole-tree, and observed-OTUs). Taken together, dietary RBC improved the growth performance of weaned piglets, and 10 g/kg RBC2 in the diet exceeded the effect of AB on the weaning piglets.